CGFTNet: Content-Guided Frequency Domain Transform Network for Face Super-Resolution - Yeerlan Yekeben; Shuli Cheng; Anyu Du (Information)
Recent advancements in face super resolution (FSR) have been propelled by deep learning techniques using convolutional neural networks (CNN). However, existing methods still struggle with effectively capturing global facial structure information, leading to reduced fidelity in reconstructed images, and often require additional manual data annotation. To overcome these challenges, we introduce a content-guided frequency domain transform network (CGFTNet) for face super-resolution tasks. The network features a channel attention-linked encoder-decoder architecture with two key components: the Frequency Domain and Reparameterized Focus Convolution Feature Enhancement module (FDRFEM) and the Content-Guided Channel Attention Fusion (CGCAF) module. FDRFEM enhances feature representation through transformation domain techniques and reparameterized focus convolution (RefConv), capturing detailed facial features and improving image quality. CGCAF dynamically adjusts feature fusion based on image content, enhancing detail restoration. Extensive evaluations across multiple datasets demonstrate that the proposed CGFTNet consistently outperforms other state-of-the-art methods.